Строение Земли: [энциклопедия / выпускающий редактор И. Ю. Фатиева] - Фатиева И. Ю. (Эрудит, 2007)
Экземпляры: ф.16 (20200904) / Инвентарный номер: 60229 / Цена: / Сис.шифр: 26.0 / Авт.знак: С 86 / ГРНТИ: 38 / ББК: 26.0я2